Inflation rate impact on the share returns of real sector companies in AP Vojvodina - Anđelić, Goran; Penezić, Nenad; Tot, Vilmoš; Milošević, Marko R. (The European Journal of Applied Economics, 2018)
Taking into account the current trends in the domestic financial market,the subject of this research is the analysis, testing and quantificationof the inflation rate impact on the daily share returns of the real sectorcompanies in AP Vojvodina. The aim of the research is to generateconcrete, practically tested and quantified knowledge about the possibilitiesand efficiency of the GARCH models application to quantifythe inflation rate impact on the share returns of the observed companies.The period covered by the survey is from 2006 to 2016 and it includesthe real sector companies of AP Vojvodina whose shares are quotedwithin the stock exchange index BELEXline. The research results showthe exact correlation between the daily return rates of the observedcompanies and the financial risk factor - the inflation rate. The resultsalso show a positive impact of the variable inflation rate on the returnsof companies NIS a.d (0.013876), Sojaprotein a.d (0.019167) and Vitala.d (0.051056), and a negative impact on the returns of the companyVeterinary Institute a.d (-0.000183). The research results confirm therole and significance of the application of econometric models in orderto quantify financial risk factors of returns from investment activitiesin the real sector companies of AP Vojvodina.
Keywords: investment; risk; real sector; GARCH models; share returns; inflation rate